2020
DOI: 10.1080/10474412.2020.1785884
|View full text |Cite
|
Sign up to set email alerts
|

Legal and Research Considerations regarding the Importance of Developing and Nurturing Trusting Family-Professional Partnerships in Special Education Consultation

Abstract: Over the past 30 years, through multiple reauthorizations, both the Every Student Succeeds Act, and the Individuals with Disabilities Education Act, lawmakers and researchers have consistently acknowledged the importance of fostering familyprofessional partnerships in schools. Yet research continues to document a number of challenges and obstacles experienced by families and professionals with actualizing this intended partnership through both special meetings (i.e., Individualized Education Programs) and ongo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…Building these partnerships can be difficult work that takes time (Beneke & Cheatham, 2016). However, even beyond this study, research has shown the benefits of positive family-professional partnerships time and again (Mueller, 2020). While none of these recommendations are new, they still are not the norm despite years of research documenting their impact and importance.…”
Section: Implications For Practicementioning
confidence: 79%
See 1 more Smart Citation
“…Building these partnerships can be difficult work that takes time (Beneke & Cheatham, 2016). However, even beyond this study, research has shown the benefits of positive family-professional partnerships time and again (Mueller, 2020). While none of these recommendations are new, they still are not the norm despite years of research documenting their impact and importance.…”
Section: Implications For Practicementioning
confidence: 79%
“…Parents may have greater satisfaction with the IEP when they feel that they have a positive partnership with the professionals on their child’s IEP team and are viewed as equal members of the team. Unfortunately, when there is no strong partnership—which is often the case, particularly for CLD families (Harry, 2008; Olivos et al, 2010) parents have negative experiences during IEP meetings (Gershwin, 2020).…”
Section: Family–professional Partnershipmentioning
confidence: 99%
“…Building trusting, collaborative relationships is the most important component of building successful and meaningful partnerships with families. 48 Trust means “having confidence in someone else’s reliability, judgment, word, and action to care for and not harm the entrusted person.” 49(p180) Final items 1 and 2 of the SHCPS-P were developed as subdimensions regarding respect for each other and trust in expertise . These align with building trust, listening to parents’ concerns, and valuing parents’ knowledge of their child.…”
Section: Discussionmentioning
confidence: 99%